An Analysis of Students’ Difficulties in Learning TOEFL at Seventh Semester of Universitas HKBP Nommensen Pematangsiantar - Herman Herman; Dumaris E Silalahi; Yanti Kristina Sinaga; Gabriella Clarisa Silaban (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The purpose of this study is to investigate the students’ difficulties in conducting the TOEFL test in the skill of structure and written expressions. Descriptive qualitative was implemented in this research with students of the seventh semester of English Department of Universitas HKBP Nommensen Pematangsiantar as the data. The result was the most difficult skills faced by the students were skill 25, it was the use parallel structure with paired conjunction, with only 3 students. Some factors causing the skill to be the most difficult was students lost their focus in managing time and they were lack of knowledge and training in practising the section of structure (grammar).